The Role of Social Media in Learning Physics: Teacher and Student Perceptions - Rika Dwi Kurniati; Doni Andra; I Wayan Distrik (Jurnal Pembelajaran Fisika, 2020)
This study aims to determine the role of social media in learning. We know that today, social media has an indispensable role in the learning process. In addition, social media has made it a smaller world through social media so that people from anywhere in the world can interact without being limited by distance and time. This study used a mixed-method consisting of qualitative and quantitative data. This research involved 308 students in Lampung province. The results of the research conducted stated that 65% of students used smartphones in learning. 73.2% of students stated that the application that is often opened is social media. 87.2% stated that the most frequently accessed social media is chatting media. 48.2% of students prefer playing on social media for learning physics. 72.3% of students stated that they prefer to discuss through chatting media. Based on the results of the preliminary study, the role of social media is very active, 48% of students stated that they use social media for learning discussions. . 43% of teachers stated that they always use social media to support learning.Keywords: social media, physics learning, smartphoneDOI: http://dx.doi.org/10.23960/jpf.v8.n2.202004